Система показників наукоємності в умовах глобілізації економіки - Яковлєв, Анатолій Іванович; Грудачова, Ольга Сергіівна; Турбаєвський, Ярослав Миколайович (НТУ "ХПІ", 2017)
Визначено склад і зміст показників наукоємності нововведень в епоху економіки знань, глобальної економіки і засоби їх розрахунку. Запропонована система відповідних кількісних і якісних показників для прикладних і фундаментальних досліджень, а також міжнародних проектів, реалізуємих в транснаціональних компаніях. Наведено таблицю збору вихідних даних для оцінки стану наукоємності в установах-розробниках інновацій.

The composition and content of the indicators of the knowledge intensity of innovations in the era of knowledge economy, the global economy and the means of their calculation are determined. A system of appropriate quantitative and qualitative indicators for applied and fundamental research, as well as international projects implemented in multinational companies, is proposed. The table of the output data collection for estimating the state of science-intensive of innovations is presented. Also, certain formulas are proposed, which are used to determine the effective and cost-effective indicators for assessing of science-intensive. Taking into account the globalization of the economy, this system of indicators makes it possible to assess science-intensive innovations rather qualitatively. Because science-intensive products are the key to a competitive enterprise, industry, and the country.
System of indicators of knowledge in tensity in the conditions of globalization of the economy
Keywords: глобальна економіка; інновації; системний підхід; транснаціональні компанії; science intensity; global economy; innovations; system approach; transnational companies